Efficacy and Tolerability of Peritendinous Hyaluronic Acid in Patients with Supraspinatus Tendinopathy: a Multicenter, Randomized, Controlled Trial - César Flores; Ramón Balius; Guillermo Álvarez; Miguel A. Buil; Luisa Varela; Carlos Cano; Joaquín Casariego (SpringerOpen, 2017)
Abstract Background Physical therapy and peritendinous hyaluronic acid (HA) injections have both shown promising results in the treatment of shoulder tendinopathies. However, the superiority of treatment combining physical therapy and HA is unclear. Methods Patients with ultrasound-confirmed supraspinatus tendinopathy were randomized to receive either physical therapy + subacromial HA injections or physical therapy only. Treatment efficacy was assessed using a Visual Analog Scale (VAS) for pain and an Activities of Daily Living (ADL) scale. Other measures were the number of rehabilitation sessions and days needed for recovery, the Tampa Scale for Kinesiophobia (TSK), and the physician and patient's perception of efficacy and tolerability. Patients were followed up for 90 days. Results Overall, VAS and ADL scores showed a progressive decrease during the follow-up (P < 0.01 at all visits for both groups), without significant differences between groups. The TSK score decreased significantly more in the HA group than in the control group (3.6 vs. 2.4; P < 0.001). Patients in the control group needed more rehabilitation sessions (28 vs. 22 in the HA group; P = 0.006) and more days for returning to their pre-injury activity (32 vs. 20 in the HA group; P = 0.013). Both patients and investigators perceived higher efficacy in the HA group than in the control group (P = 0.034). Both treatments were safe and well tolerated. Conclusions Subacromial HA injections combined with physical therapy have high efficacy in the treatment of supraspinatus tendinopathy, leading to an earlier return to pre-injury activity and the need for fewer rehabilitation sessions, which may benefit both patients and the healthcare system.